(3eONd aj CMcGe GdfLhes - (3YHO GdYRjR Hf YKeGf GdbHjUj GdgGTej, CHh GdUbQ,J (B380 (3g` s
(3ChdgG (B:s
(3GeG HYO aEfi deG QCjJ LeGYI ef eJbOei UfGYI CMcGe GdfLhe s
(3BNQgG (B:s
(3HGH ai UaI GdRgGO agPg TQhW GdRGgO JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdKGdKs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B22 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B252s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1642s
(3eUOQ GbJfGA GdCUd (B:s
(3ceHQOL (B(15) s
Keywords: (3CUhd Gdabgs